Challenges Of The Industrial Relations Court In The Reform Era In Creating Fast, Accurate, Fair And Cheap Court - Rika Jamin Marbun (Yayasan Multidimensi Kreatif, 2024)
The Industrial Relations Court is a special court with absolute competence in dealing with industrial relations disputes arising from work relations between workers/laborers and employers. As the last resort in resolving employment conflicts if non-litigation channels fail, this court is expected to provide a fast, precise, fair and inexpensive resolution process for the parties so that it becomes the best solution. However, in practice, the existence of the industrial relations court has not fully become a mechanism that can realize the urgency of the court's existence since its inception. Various obstacles often arise and are even unavoidable in relation to the substance and mechanisms that hinder the realization of the initial intention of establishing the overarching law, namely Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes. This research explains the various challenges faced by the Industrial Relations Court since its formation until the post-reform period. The research method of implementing literature studies and the type of research is normative law by compiling and reviewing various normative provisions regarding industrial relations courts and problems in their application. Industrial relations courts face various challenges related to their substance and mechanisms, for example when they are at the decision implementation stage, it is quite difficult to carry out the execution because they are guided by the execution procedures in civil courts which are quite expensive and time consuming. Meanwhile, industrial relations issues are ideally oriented towards fast processes and low costs. On the other hand, from the data on registered dispute cases, the worker/laborer mostly acts as a plaintiff, meaning that even if the plaintiff in this case wins, the court decision is not yet able to fully grant the worker/laborer their maximum rights.